Do cooperative enterprises create social trust? - Fabio Sabatini; Francesca Modena; Ermanno Tortia (Economics and Econometrics Research Institute (EERI), 2012)
This paper contributes to the literature by carrying out the first empirical investigation into the role of different types of enterprises in the creation of social trust. Drawing on a unique dataset collected through the administration of a questionnaire to a representative sample of the population of the Italian Province of Trento in March 2011, we find that cooperatives are the only type of enterprise where the work environment fosters the social trust of workers.
Keywords: L31; L33; P13; Z1; Z13; 330; Cooperative enterprises; nonprofit organizations; trust; social capital; motivations; inclusive governance; work organization